The Effect of Different Carbapenem Antibiotics (Ertapenem, Imipenem/Cilastatin, and Meropenem) on Serum Valproic Acid Concentrations. Issue 5 (October 2016) - Wu, Chien-Chih; Pai, Tsung-Yu; Hsiao, Fei-Yuan; Shen, Li-Jiuan; Wu, Fe-Lin Lin
Abstract : Background: Carbapenem antibiotics (CBPMs) may significantly reduce the serum concentration of valproic acid (VPA), but the extent of this effect among various CBPMs is unknown. This study compared the extent and onset of the interactions among ertapenem, imipenem/cilastatin, and meropenem. Methods: A 5-year retrospective study was performed. Hospitalized patients over 18 years old who received VPA and a CBPM concurrently were enrolled via the pharmacy computer system. Patients who lacked VPA serum concentration measurements before or during CBPMs' use, had concurrent medication(s) that might interfere with VPA metabolism, or had a history of liver cirrhosis were excluded. Total VPA serum concentrations before and during CBPMs' use and after its discontinuation were recorded, and differences among various CBPMs were analyzed. Results: Fifty-two patients were included in this analysis. Irrespective of the route of administration, VPA serum concentrations were subtherapeutic in 90% of the subjects during CBPMs' use. There was a significant decrease ( P < 0.001) in VPA serum concentrations during the use of CBPMs: 72% ± 17%, 42% ± 22%, and 67% ± 19% in the ertapenem (N = 9), imipenem/cilastatin (N = 17), and meropenem (N = 26) groups, respectively. The effect of ertapenem and meropenem on VPA was significantly more expressed than that of imipenem/cilastatin ( P < 0.005). The onset of this drug interaction occurred within 24 hours of CBPMs' administration, and VPA serum concentrations returned to 90% of baseline within 7 days of CBPMs' discontinuation along with a 20% increase in VPA dose. Increasing VPA dose during the use of ertapenem or meropenem did not result in elevating VPA serum concentrations to therapeutic levels during the combined therapy period. Conclusions: CBPMs reduced VPA serum concentration within 24 hours of administration by approximately 60%. Ertapenem and meropenem had a greater effect on VPA serum concentration than imipenem/cilastatin. Because of the dramatic reduction of VPA serum concentration during CBPMs' use, concomitant use of VPA and CBPMs should be avoided.